Forecasting the impact of global warming on soil bacterial communities using simulated systems - Lau, Grace Xin Hui; Fan, Hui Yin; Abdul Halim, Mardani; Cheah, Yoke Kqueen; Wong, Clemente Michael Vui Ling (Universiti Sains Malaysia, 2024)
Recently, global warming has become more visible, and the entire world is experiencing its effects. Given that global temperature is rising by 0.2 °C (± 0.1 °C) per decade, human-induced warming reached 1 °C above pre-industrial levels around 2017 and is expected to reach 1.5 °C around 2040. However, there is a lack of comprehensive data and long-term monitoring studies on how global warming might impact the diversity of bacteria in terrestrial ecosystems. Since bacteria have a specific range of temperatures for optimal growth and metabolic activity, changes in surrounding temperature may induce a change in soil temperature, leading to alterations in the diversity and composition of soil bacterial communities. Considering the vital ecological functions performed by terrestrial soil bacteria, it is crucial to understand how terrestrial bacteria respond to elevated environmental temperatures. This knowledge will facilitate the development of appropriate intervention strategies to address the anticipated depletion of beneficial bacteria and the potential increase in pathogenic soil bacteria in the upcoming years. This review paper explores researchers’ efforts over many years to document bacterial diversity and to forecast the impact of global warming on soil bacterial communities using various simulation systems. It also discusses potential mitigation strategies for preserving the pre-warming healthy soil bacteria communities.